Telaah Pemikiran Ibnu Khaldun Tentang Upah: Refleksi Terhadap Sistem Pengupahan Nasional - Novita Akria Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article examines Ibn Khaldun's philosophical perspective on wages and its relevance to the wage system in Indonesia in the modern era. Ibn Khaldun, a prominent 14th-century Muslim thinker, emphasized that wages are closely linked to the value of work, social justice, and the economic stability of a society. In his Muqaddimah, he emphasized that establishing fair wages is not merely an economic issue but also a moral and social pillar that can prevent societal disintegration. Equitable wages, he argued, must be able to guarantee a decent living for workers and their families, while also supporting continued productivity and social cohesion. This study uses a qualitative normative approach through content analysis of relevant texts in the Muqaddimah and comparing them with wage policies in Indonesia, including minimum wage regulations, labor protection, and welfare policies. Data were obtained from library research, national regulations, and recent academic literature on wage policies. The results of the study indicate that although Indonesia has a minimum wage regulation, its implementation still faces significant challenges, particularly in ensuring fairness for informal sector and low-income workers. Factors such as regional economic inequality, inflation, and weak labor oversight often undermine the effectiveness of these policies. By revisiting the principles of Ibn Khaldun, this article offers the perspective that ideal wages should not only be measured by labor market needs but should also integrate principles of ethics, morality, and social responsibility. This integration is expected to strengthen worker welfare, increase national productivity, and maintain long-term economic stability. This study also provides a relevant philosophical framework for critiquing and reforming wage policies in Indonesia, with reference to the values of justice and welfare in classical Islamic economics.